CORRIGENDUM TO “INVESTIGATION OF CONVENTIONAL AND ASPHALTIC UNDERLAYMENT TRACK BEHAVIORS SUBJECTED TO FREIGHT TRAIN LOAD: MECHANISTIC APPROACH” (Journal of Applied Engineering Science, 2023)
CLARIFICATIONThe authors affiliation was misprinted within the article in subject published in 20(2022)3, 974, 673-687, DOI:10.5937/jaes0-35499. Authors’ affiliation should be corrected as follows:Dian M. SetiawanDepartment of Civil Engineering, Universitas Muhammadiyah Yogyakarta, Jl. Brawijaya, Bantul, Yogyakarta, Indonesia*diansetiawanm@ft.umy.ac.idThis addition does not affect the original paper. We apologize for any inconvenience that this may have caused.